1996
DOI: 10.1046/j.1471-4159.1996.67041770.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Nitric Oxide Synthase Inhibitor, 7‐Nitroindazole, Protects Against Methamphetamine‐Induced Neurotoxicity In Vivo

Abstract: The present study was undertaken to investigate whether the relatively selective neuronal nitric oxide synthase (NOS) inhibitor, 7‐nitroindazole (7‐NI), protects against methamphetamine (METH)‐induced neurotoxicity. Male Swiss Webster mice received the following treatments (i.p.; q 3 h × 3): (a) vehicle/saline, (b) 7‐NI (25 mg/kg)/saline, (c) vehicle/METH (5 mg/kg), and (d) 7‐NI (25 mg/kg)/METH (5 mg/kg). On the second day, groups (a) and (b) received two vehicle injections, and groups (c) and (d) received two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
105
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 165 publications
(107 citation statements)
references
References 16 publications
1
105
0
1
Order By: Relevance
“…The protective effects of 7-NI and other nNOS inhibitors against METH-induced dopaminergic neurotoxicity were independent of METH-induced hyperthermia (Itzhak and Ali 1996;Itzhak et al 2000). Likewise, another selective nNOS inhibitor, AR-R17477AR, attenuated the depletion of DA and the neurofilament protein NF68, but not the hyperthermia, caused by METH (Sanchez et al 2003).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The protective effects of 7-NI and other nNOS inhibitors against METH-induced dopaminergic neurotoxicity were independent of METH-induced hyperthermia (Itzhak and Ali 1996;Itzhak et al 2000). Likewise, another selective nNOS inhibitor, AR-R17477AR, attenuated the depletion of DA and the neurofilament protein NF68, but not the hyperthermia, caused by METH (Sanchez et al 2003).…”
Section: Discussionmentioning
confidence: 92%
“…The interval between paired injections was 30 min, and each pair of injections was separated by 4-5 h. The dose of the nNOS inhibitor was based on our previous studies which showed that 25 mg/kg 7-NI inhibited about 80% of mouse brain NOS activity (Itzhak 1996) and attenuated METH-induced dopaminergic neurotoxicity in Swiss Webster mice (Itzhak and Ali 1996). In the second experiment, nNOS(-/-) and wild-type (WT) mice (n ¼ 10-12 per group) received saline or fenfluramine (25 mg/kg), twice a day for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations